Combating IUU fishing: an examination of interaction between China and regional fisheries management organizations - Li, Shuo (Frontiers in Marine Science, 2025)
This paper examines China’s evolving engagement with Regional Fisheries Management Organizations (RFMOs) in addressing illegal, unreported, and unregulated (IUU) fishing. As the world’s largest fishing nation, China’s cooperation is crucial to achieving global fisheries sustainability. Through an analysis of legal instruments and case studies across eight RFMOs in which China participates, the study finds that China has progressively aligned its domestic regulations with RFMO measures—such as vessel licensing systems, observer programs, and IUU vessel blacklists. The incorporation of RFMO obligations into its national legislation, along with China’s cooperative approach toward RFMOs of which it is not a member, reflects a growing commitment to international fisheries governance. However, challenges remain. While China has actively engaged in RFMO decision-making processes, its cautious stance on certain issues highlights ongoing tensions both among member states and between states and international institutions. This study concludes that China’s regulatory reforms have enhanced its compliance and demonstrated its commitment to sustainable fisheries. However, further improvements in transparency and a more proactive role in international cooperation remain necessary. RFMOs provide valuable platforms for collaborative governance, and strengthening deeper and effective participation is essential to enhancing their overall function